The Filipinos are grateful to the United States (A radio interview). (Filipiniana Reference Shelf : A compilation of selected speeches, orations, debates, articles and essays about the Philippines)
Transcript of radio conversation between President Manuel L. Quezon and United States High Commissioner Paul V. McNutt regarding the Philippines' gratefulness towards the United States' altruistic works. Broadcast over Station KZRM-Radio Manila, and in the United States through the NBC network on 13 August 1938.